Advanced research on mechanical and electronic information engineering II : selected, peer reviewed papers from the 2014 2nd International Conference on Mechanical and Electronic Engineering (ICMEE 2014), June 21-22, 2014, Wuhan, China - Zhang, Helen; Jin, David; Zhao, X. J. (Advanced materials research ;, 2014)
Collection of selected, peer reviewed papers from the 2014 2nd International Conference on Mechanical and Electronic Engineering (ICMEE 2014), June 21-22, 2014, Wuhan, China. The 60 papers are grouped as follows: Chapter 1: Materials Science, Processing and Application, Chapter 2: Applied Mechanics, Mechanical and Electronic Engineering Research, Chapter 3: Environmental Research and Energy Engineering, Chapter 4: Computation and Information Technologies Keyword: materials science, mechanical engineering, mechanical automation, information technology, electronics, applied technology Engineers and other researchers from China and Taiwan present 60 papers from the 2014 2nd International Conference on Mechanical and Electronic Engineering (ICMEE 2014), which was held in June of that year in Wuhan, China. Topics relate to materials science, processing, and application; applied mechanics, mechanical, and electronic engineering; environmental research and energy engineering; and computation and information technologies. -- Energy engineering-- Materials science-- Mechanical engineering.